A new genus of trechine beetles, Puertrechus gen. n., with two new species and a new species of Dactylotrechus Belousov et Kabak, 2003 from Southern China (Coleoptera: Carabidae: Trechinae) - Belousov, Igor A.; Kabak, Ilya I. (Zootaxa, 2014)
Puertrechus gen. n., related to both Dactylotrechus and Quiennectrechus Deuve, 1992 is established to accommodate two new trechine species: P. mengsaensis sp. n. (type species of the genus, type locality: Mountains East of Mengsa City, Lincang Prefecture, Yunnan, China) and P. daxueshanicus sp. n. (type locality: Daxueshan Mount, the same prefecture). Likewise, the second species of the genus Dactylotrechus Belousov & Kabak, 2003, D. yalongensis sp. n., is described from the right bank of the Yalong River, SW of Mianing, southern Sichuan, China. This species differs from the only known species of the genus in some important characters including the elytral chaetotaxy and the male genitalia structure. Some adjustments of the genus diagnosis are made to embrace the new species. Keys to species of Dactylotrechus and Puertrechus gen. n. are included and their distribution is mapped. A key is provided to differentiate Puertrechus , Dactylotrechus and Quiennectrechus.